Improving early literacy through teacher professional development: Experimental evidence from Colombia - Horacio Alvarez Marinelli; Samuel G. Berlinski; Matias Busso; Julian Martinez-Correa (Inter-American Development Bank (IDB), 2022)
Teachers are the most fundamental input of students' learning. For this reason, developing teaching skills is a policy priority for most governments around the world. We experimentally evaluate the effectiveness of "Let's All Learn to Read," a one-year professional development program that trained and coached teachers throughout the school year and provided them and their students with structured materials. Following a year of instruction by the trained teachers, students' literacy scores in treated schools grew by 0.386 of a standard deviation compared to students in the control group. These gains persisted through the second and third grades. We also show that an early intervention in first grade is more cost-effective at improving literacy skills than implementing remediation strategies in third grade.
Keywords: I20; H52; O15; 330; Teacher professional development; Early Interventions; Literacy; Colombia